Echocardiographic speckle tracking provides incremental value for left atrial function in patients with paroxysmal atrial fibrillation. (8th February 2021) - Bastos, L; Al-Khalili, F; Back, M; Manouras, A; Engdahl, J; Shahgaldi, K
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Danderyds Hospital Background: Atrial fibrillation (AF) is associated with progression of left atrial (LA) structural and functional changes. It is well acknowledged that AF over time promotes LA enlargement. Transthoracic echocardiography (TTE) is important in decision making for further treatment. Initially, new onset of AF such as paroxysmal AF can occur in the absence of LA enlargement. Therefore assessment of LA volume index (LAVI) as follow-up can mislead LA evaluation. LA global longitudinal strain (LA-GLS) is a novel parameter assessed with two-dimensional (2D) speckle tracking (ST). LA-GLS allows quantification of LA myocardial deformation by measuring reservoir function which reflects LA compliance during left ventricular systole. Purpose: Our aim is to study potential differences in LA myocardial deformation as assessed by LA-GLS in paroxysmal AF patients compared with aged-matched control group. Methods: A total of 75 paroxysmal AF patients and 99 control aged-matched patients (mean age, 77 ± 0.4) were enrolled from STROKESTOP2 study. Patients with paroxysmal AF were included from a subgroup of newly screened-diagnosed AF. TTE examinations were analyzed retrospectively offline using dedicated software. NT-proBNP ≤ 900 ng/L was an inclusion criteria. Besides conventional echocardiographic parameters, LA-GLS was measured using 2D-ST in biplane during systole. Results: There was a significant LA-GLS reduction in the paroxysmal AF group compared to the control group (19 ± 6.1 % vs. 28 ± 7.2 %, P < 0.001) with a feasibility of 70 %. In the AF group, 45 patients (60 %) expressed normal LAVI <34 ml/m2. No significant difference was revealed concerning LAVI (P > 0.05) between the groups (AF group with normal LAVI), yet LA-GLS remained significant reduced in the AF group (P < 0.001). No significant difference was shown regarding NT-proBNP levels (P > 0.05) between the AF group 243 (179-420) ng/L and the control group 219 (160-317) ng/L. Conclusion: LA-GLS allows early detection of LA myocardial deformation dysfunction before LA enlargement in patients with paroxysmal AF. This findig provides incremental information to conventional echocardiographic parameters of LA. Whether early detection of LA dysfunction using LA-GLS can contribute to better risk stratification and cardiac therapy improvement requires to be further investigated.